A multiple stakeholder perspective of the television advertising production process in Malaysia - Mokhtar, Aida (2012)
Communication plays a big role in nation building (Taylor and Kent 2006). Television advertising is powerful. It has movie-like qualities which bring stories to life and create powerful brand imagery (Moriarty, Mitchell et al. 2012). There has been a dearth of studies on the television advertising production process. It is hoped that this study which examines the television advertising production process in Malaysia from the multiple stakeholder perspective for responsible advertising (Polonsky and Hyman 2007) contributes to the gap in advertising research.